Poetics of place: rural and urban space in the prose of D. H. Lawrence - Stehlíková, Nikol (Univerzita Pardubice, 2009)
The work deals with conception of space in the prose of D. H. Lawrence. The theoretical part specifies the main features of modernism and the practical part elaborates the conception of space in three Lawrence´s novels and two short stories. The aim of this work is to reveal what meanings and symbols Lawrence ascribes to particular spaces and what stories he sets in them.
Keywords: D. H. Lawrence; Modernism; urban space; rural space; natural space; D. H. Lawrence; Modernismus; města; venkov; příroda